Sanguinarine Reverses Pulmonary Vascular Remolding of Hypoxia-Induced PH via Survivin/HIF1α-Attenuating Kv Channels - Fan, Fenling; Zou, Yifan; Wang, Yousen; Zhang, Peng; Wang, Xiaoyu; Dart, Anthony M.; Zou, Yuliang (Frontiers in Pharmacology, 2021)
Background: Similarities in the biology of pulmonary hypertension and cancer suggest that anticancer therapies, such as sanguinarine, may also be effective in treating pulmonary hypertension. This, along with underlying biochemical pathways, is investigated in this study. Methods: Rats were subjected to 4-week hypoxia (or control) with or without sanguinarine treatment. In addition, pulmonary artery smooth muscle cells (PASMCs) were examined after 24–48 h hypoxia (with normoxic controls) and with or without sanguinirine. Pulmonary artery pressures and plasma survivin levels were measured in vivo. Ex vivo tissues were examined histologically with appropriate staining. mRNA and protein levels of survivin, HIF-1α, TGFb1, BMPR2, Smad3, P53, and Kv 1.2, 1.5, 2.1 were determined by real-time PCR and Western blot in PASMCs and distal PAs tissue. PASMC proliferation and changes of TGFb1 and pSmad3 induced by sanguinarine were studied using MTT and Western blot. Electrophysiology for Kv functions was measured by patch-clamp experiments. Results: Four-week hypoxia resulted in an increase in serum survivin and HIF-1α, pulmonary artery pressures, and pulmonary vascular remodeling with hypertrophy. These changes were all decreased by treatment with sanguinarine. Hypoxia induced a rise of proliferation in PASMCs which was prevented by sanguinarine treatment. Hypoxic PASMCs had elevated TGFb1, pSmad3, BMPR2, and HIF1α. These increases were all ameliorated by sanguinarine treatment. Hypoxia treatment resulted in reduced expression and function of Kv 1.2, 1.5, 2.1 channels, and these changes were also modulated by sanguinarine. Conclusion: Sanguinarine is effective in modulating hypoxic pulmonary vascular hypertrophy via the survivin pathway and Kv channels.